Dectin-1-Mediated Production of Pro-Inflammatory Cytokines Induced by Yeast β-Glucans in Bovine Monocytes - Pedro, Ana R. V.; Lima, Tânia; Fróis-Martins, Ricardo; Leal, Bárbara; Ramos, Isabel C.; Martins, Elisabete G.; Cabrita, Ana R. J.; Fonseca, António J. M.; Maia, Margarida R. G.; Vilanova, Manuel; Correia, Alexandra (Frontiers in Immunology, 2021)
Yeast-derived products containing β-glucans have long been used as feed supplements in domesticated animals in an attempt to increase immunity. β-glucans are mainly recognized by the cell surface receptor CLEC7A, also designated Dectin-1. Although the immune mechanisms elicited through Dectin-1 activation have been studied in detail in mice and humans, they are poorly understood in other species. Here, we evaluated the response of bovine monocytes to soluble and particulate purified β-glucans, and also to Zymosan. Our results show that particulate, but not soluble β-glucans, can upregulate the surface expression of costimulatory molecules CD80 and CD86 on bovine monocytes. In addition, stimulated cells increased production of IL-8 and of TNFA and IL6 mRNA expression, in a dose-dependent manner, which correlated positively with CLEC7A gene expression. Production of IL-8 decreased significantly after CLEC7A knockdown using two different pairs of SiRNAs. Overall, we demonstrated here that bovine monocytes respond to particulate β-glucans, through Dectin-1, by increasing the expression of pro-inflammatory cytokines. Our data support further studies in cattle on the induction of trained immunity using dietary β-glucans.